Strategi Branding dan Pemasaran Digital untuk Meningkatkan Penjualan Produk pada UMKM Mins di Pasar Digital - Arum Andini; Ridwan Ridwan; Rohmalia Putri; Dwi Salwa; Idam Idam; Daffa Owen (BADAN PENERBIT STIEPARI PRESS, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) play a crucial role in the Indonesian economy by making substantial contributions to employment and the country's GDP. However, marketing still faces significant obstacles, particularly in the digital age where quick technological adaptability is required. The purpose of this study is to evaluate how branding and digital marketing tactics are being used at Mins Maemon MSMEs and to find ways to make them more successful. Through literature reviews, in-depth interviews with MSME participants and consumers, and observation, the study employs a qualitative approach with a case study methodology. The findings demonstrate how e-commerce platforms, social media, and visually appealing content can all be used to enhance digital branding strategies and boost product visibility and sales. However, difficulties such a lack of content The optimization of digital initiatives is still hampered by issues like time management and a lack of content ideas. Possible remedies include influencer cooperation, content calendar development, and training. In conclusion, MSMEs must have a well-organized and consistent digital strategy in order to succeed when competing in the digital market.